Konsumsi Jantung Pisang sebagai Galaktagog Lokal terhadap Peningkatan Berat dan Tinggi Badan Bayi Usia 0–6 Bulan: A Quasi Experimental - Wilda Yunita; Nurhaida Br. Kaban (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The banana blossom has significant potential as a local superfood that can enhance both the production and quality of breast milk (ASI). Its nutritional components—including plant-based proteins, fiber, minerals, and phytonutrients—make it a safe, natural, and easily accessible alternative source of nutrition across various regions of Indonesia. This study is particularly important given the persistently high prevalence of nutritional problems among infants and the low rate of exclusive breastfeeding in the country.The development of banana blossom–based food innovations is expected to serve as an effective strategy to strengthen household food security and address nutritional challenges among vulnerable groups, particularly breastfeeding mothers and infants in their early stages of life. The purpose of this study is to examine the potential effects of banana blossom consumption on optimizing the growth and development of infants aged 0–6 months. This research employs an experimental design using a pre–post-test control group method. The participants consist of 40 breastfeeding mothers with infants aged 0–6 months within the working area of Puskesmas Stabat, Medan. The intervention group received banana blossom consumption every three days for four weeks. The results show that banana blossom consumption had a significant effect on increasing infants’ weight and height, indicating its potential contribution to sustainably improving infant nutritional status.